2016
DOI: 10.1061/(asce)wr.1943-5452.0000591
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Seasonal Time Series Models to Forecast Short-Term Water Demand

Abstract: This paper presents a methodology to forecast short-term water demands either offline or online by combining SARIMA (seasonal autoregressive integrated moving average) models with data assimilation. In offline mode, the method frequently re-estimates the models using the latest historical data. In online mode, the method applies a Kalman filter to optimally and efficiently update the models using a real-time feed of data. The tailoring process consists of identifying, estimating and validating the models, alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…Sub-hourly, hourly, and daily water predictions were provided by the approach presented in [25]. In particular, the approach was based on coupled Seasonal ARIMA (SARIMA) models with data assimilation that were tailored to be applied to three different datasets (all of them with different quality characteristics).…”
Section: Related Workmentioning
confidence: 99%
“…Sub-hourly, hourly, and daily water predictions were provided by the approach presented in [25]. In particular, the approach was based on coupled Seasonal ARIMA (SARIMA) models with data assimilation that were tailored to be applied to three different datasets (all of them with different quality characteristics).…”
Section: Related Workmentioning
confidence: 99%
“…For descriptive purposes, the parameter estimation only needs to be conducted once. However, for long‐term forecasting purposes, the parameters may be prone to changes (e.g., Arandia‐Perez et al () demonstrated that updating the parameters of a single‐seasonal ARIMA at fixed time intervals improved performance), and an efficient change detection method is useful in determining the correct timing for parameter reestimation. The change detection problem in correlated time series data were studied by Basseville and Nikiforov () and Lai () in which the Generalized Likelihood Ratio (GLR) algorithm was proposed.…”
Section: Model Identification Parameter Estimation and Forecastingmentioning
confidence: 99%
“…Arandia‐Perez () evaluated aggregated demands collected from a regional area within Cincinnati, OH, and demonstrated that single‐seasonal ARIMA models (including either 24 h or weekly periodicities) could describe hourly regional water demands. More recently, Arandia‐Perez et al () compared the performance of single‐seasonal ARIMA models on total system and regional aggregated demands using 15 min, 1 h, and 24 h demand data from Dublin, Ireland, which included an extended Kalman filtering updating process at fixed time intervals. These results demonstrated that the performance of the seasonal ARIMA models improved with larger spatial aggregation and reestimation of the model parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Arandia et al [33] proposed a methodology to predict 15 min, hourly, and daily water demand either offline (using historical data) or online (using a real-time feed of data). eir proposal joined seasonal ARIMA (SARIMA) and data assimilation.…”
mentioning
confidence: 99%